EFEKTIVITAS DAKWAH BERBASIS HUMOR: STUDI KASUS DI DAERAH MANDAILING NATAL - Fitri Ani Aulia Rangkuti; Ilmi Khodijah; Nur Prasanti; Riski Deliana; Siti Rahma Harahap (Prodi Manajemen Dakwah STAIN Mandailing Natal, 2024)
Humor-based da'wah is a new approach in conveying Islamic religious teachings that uses elements of humor as a means to attract the audience's attention. This study aims to explore the effectiveness of humor-based da'wah in the Mandailing Natal area, North Sumatra. The research method used is qualitative with a case study approach. Data was collected through in- depth interviews with religious leaders, traditional leaders and the general public who were involved in humor-based da'wah activities. Data analysis was carried out using a thematic approach to identify general patterns in responses and perceptions of this community's preaching